Photography through the process files: reflections on the publication of the contact sheets - Soares, Camila Mangueira; Fava, Fabrício Mário Maia (PORTO ARTE: Revista de Artes Visuais, 2017)
Based on the current recurrence of publications and discussions related to the materials of photographic creation process, this article presents an investigation on the contact sheets as an information material pertinent to the complexity of the making and, thus, thought in photography. Therefore, the analysis focuses on the contact sheets published in the books Magnum Contacts and Proof and the DVDs Contacts. The study took place under the theoretical perspective of the process criticism proposed by Cecilia Salles, which, based on Peircean semiotics, presents itself as a mean of perception of photography beyond the idea of product, enabling its understanding from the relations of interconnection and interaction between thought and materialities.